EFFECT OF ROSUVASTATIN ON CAROTID INTIMAMEDIA THICKNESS IN PATIENTS WITH CORONARY ARTERY DISEASE OF DIFFERENT GENDER AND CARDIOVASCULAR RISK PROFILE - S. I. Kononov; G. S. Mal (Фармация и фармакология (Пятигорск))
Secondary prevention in patients with coronary artery disease (CAD) is provided by the use of statins, as well as by the impact on modiable risk factors. Rosuvastatin causes the regression of intima-media thickness (IMT) of common carotid artery (CCA), which is signicantly associated with CAD. The aim of the study was to evaluate the change in carotid intima-media thickness (CIMT) in patients with CAD of different gender, and having different number of cardiovascular risk factors, provided that patients attain target levels of total cholesterol (TC<4.0 mmol/l) and low density lipoprotein-cholesterol (LDL-C><1.8 mmol/l). Materials and methods. 72 patients with CAD: Stable angina of functional Classes II–III were recruited. They were treated with rosuvastatin, with gradual increase of its dose from 5 to 40 mg daily to attain target levels of TC and LDL-C. Maximum CIMT was assessed at the time of inclusion into the study and after 12 months of therapy. Results and discussion. In conditions of attaining target TC and LDL-C levels, maximum CIMT signi cantly decreased both in men (p=0,006) and in women (p=0,002), the latter had lower CIMT (p=0,03) than men after 1 year of therapy, taking into account no difference in baseline values. The patients who had 2 or fewer risk factors (RF) (hypertension, a family history of cardiovascular disease, smoking, obesity, diabetes mellitus were taken into consideration) showed decrease in CIMT (p=0.0001), and those who were characterized by 3 or more RF, showed only lack of its growth (p=0.07). Attained lipid levels in the compared groups of different gender and number of RF did not differ. Conclusion. The study revealed the differences in the change of CIMT in patients with CAD of different sex, and of different number of cardiovascular risk factors. Keywords: coronary artery disease, rosuvastatin, carotid intima-media thickness, gender, cardiovascular risk factor ><4.0 mmol/l) and low density lipoprotein-cholesterol (LDL-C<1.8 mmol/l). Materials and methods. 72 patients with CAD: Stable angina of functional Classes II–III were recruited. They were treated with rosuvastatin, with gradual increase of its dose from 5 to 40 mg daily to attain target levels of TC and LDL-C. Maximum CIMT was assessed at the time of inclusion into the study and after 12 months of therapy. Results and discussion. In conditions of attaining target TC and LDL-C levels, maximum CIMT signicantly decreased both in men (p=0,006) and in women (p=0,002), the latter had lower CIMT (p=0,03) than men after 1 year of therapy, taking into account no difference in baseline values. The patients who had 2 or fewer risk factors (RF) (hypertension, a family history of cardiovascular disease, smoking, obesity, diabetes mellitus were taken into consideration) showed decrease in CIMT (p=0.0001), and those who were characterized by 3 or more RF, showed only lack of its growth (p=0.07). Attained lipid levels in the compared groups of different gender and number of RF did not differ. Conclusion. The study revealed the differences in the change of CIMT in patients with CAD of different sex, and of different number of cardiovascular risk factors.